Spatio-temporal assessment of agricultural drought using remote sensing and ground-based data indices in the Northern Ethiopian Highland - Kassahun Tenebo Alito; Mulu Sewinet Kerebih (Journal of Hydrology: Regional Studies, 2024)
Study region: Northern Ethiopian highland, North Wollo, Ethiopia Study focus: Drought is one of the most serious environmental and socioeconomic problems of Sub-Sahara Africa's countries. The study aims to assess and evaluate the agricultural drought occurrence and its severity by using remote sensing-based multivariate indices to provide real-time spatial-temporal information for drought monitoring. Satellite datasets from Landsat images with a spatial resolution of 30 m were processed and rescaled to compute vegetation and temperature indices and derive drought status indices. The temporal and spatial variability of drought were detected and mapped by using satellite-based drought indices and validated by available in-situ data. New hydrological insights for the region: The study revealed that the area was exposed to extreme drought in 1984, 2009, and 2014. On the contrary, no longer extreme drought dominated in 1989, 1994, 1999, and 2004. Moreover, the relationships between various indices have been examined by using a linear regression model. It has been detected that there is a significant strong relationship between NDVI and LST (R2 /p = 0.93/0.00), VCI and TCI (R2 /p = 0.71/0.00), VHI and SPI (R2/p = 0.85/0.00). Therefore, the spatial extent and temporal assessment of drought-related information are important for decision-making in the field of agriculture.